1981
DOI: 10.1104/pp.67.4.711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and BASF 13 338 on the Lipid Composition and Respiration of Wheat Roots

Abstract: The fatty acid composition of wheat seedling roots changed in response to temperature. As temperature declined, the level of linolenic acid increased and the level of linoleic acid decreased. The distribution of phospholipid classes was not influenced by temperature. Phosphatidyl choline and phosphatidyl ethanolamine were the predominant phospholipids isolated and comprised 85% of the total lipid phosphorus. Smaller quantities of phosphatidyl glycerol, phosphatidyl inositol, phosphatidic acid, and phosphatidyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Substituted pyridazinones including norflurazon were reported to affect lipid synthesis through inhibition of fatty acid desaturases (St John 1976, St John et al 1979, Ashworth et al 1981, Wang et al 1987) and therefore these compounds may have profound effects that are independent of effects on carotenoid or ABA synthesis. This might explain some of their effects observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Substituted pyridazinones including norflurazon were reported to affect lipid synthesis through inhibition of fatty acid desaturases (St John 1976, St John et al 1979, Ashworth et al 1981, Wang et al 1987) and therefore these compounds may have profound effects that are independent of effects on carotenoid or ABA synthesis. This might explain some of their effects observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the lipid profiling of a particular lipid class or more complicated lipidome analyses upon cold stress in wheat [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In [ 36 ], Roche et al studied the phospholipid content of seedlings grown at 2 °C and reported that the content was higher than that of seedlings grown at 24 °C.…”
Section: Introductionmentioning
confidence: 99%
“…In [ 36 ], Roche et al studied the phospholipid content of seedlings grown at 2 °C and reported that the content was higher than that of seedlings grown at 24 °C. Ashworth et al [ 37 ] reported the decrease of linoleic acid but increase in linolenic acid in wheat seedling roots in response to declined temperature, while phospholipid was not influenced by temperature. Vigh et al [ 38 ] studied the correlation of glycolipids and fatty acids of chloroplast thylakoid membranes in two wheat varieties of contrasting hardiness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental stimuli such as cold exposure or chronic dietary changes influence cellular responses, for instance, altered energy balance, gene expression, and composition or fluidity of lipid membranes 1 6 . It has previously been shown in various organisms that exposure to cold stimulates an increase in fat utilization 7 , 8 and causes alterations in membrane fluidity through incorporation of unsaturated fatty acids into lipid membranes 9 , 10 . In addition, cold exposure also causes activation of the desaturase system 11 .…”
Section: Introductionmentioning
confidence: 99%